Classical music : expect the unexpected - Nagano, Kent, 1951-; Kloepfer, Inge, 1964- (McGill-Queen's University Press, 2019)
"How relevant is classical music today? The genre seems in danger of becoming nothing more than a hobby for the social elite. Yet Kent Nagano has another world in mind, one where everyone has access to classical music. In Expect the unexpected, the famous classical composer and conductor tells the deeply personal story of his own engagement with the masterpieces and great composers of classical music, his work with the world's major orchestras, and his tireless commitment to bringing his music to everybody. Narrating his first childhood encounters with music's power to overcome social and ethnic boundaries, he celebrates an art form that has always taken part in debates about human values and societal developments. The loss of classical music, he argues, not only would impover-ish society from a cultural perspective, but would rob it of inspiration, wit, emotional depth, and a sense of community. Getting to grips with classical music's existential crisis, Nagano contends that it is too crucial to humanitys̉ survival to be allowed to disappear from our everyday reality. In this moving autobiography, Kent Nagano makes a compelling plea for classical music that is as exhilarating as it is thought-provoking."--